2010
DOI: 10.4104/pcrj.2010.00001
|View full text |Cite
|
Sign up to set email alerts
|

Economic analyses comparing tiotropium with ipratropium or salmeterol in UK patients with COPD

Abstract: Aims: This study presents a cost-effectiveness and budget impact analysis comparing cost and outcomes for UK patients with COPD treated with either tiotropium, ipratropium or salmeterol.Methods: A previously-published COPD cost-effectiveness model was adapted for the UK, then used to estimate the cost-effectiveness of tiotropium compared to salmeterol and ipratropium. Additional epidemiological data were used to estimate the budget impact of switching patients from ipratropium or salmeterol to tiotropium.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…There were 16 cost-effectiveness studies that used empirical analysis of clinical trial data of individual patients, [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] 14 studies that used Markov modelling, [44][45][46][47][48][49][50][51][52][53][54][55][56][57] and eight that used empirical analysis based on observational data. [58][59][60][61][62][63][64][65] Two studies have used a different approach, such as extrapolating the resource use reduction that was obtained after meta-analyses of clinical trials.…”
Section: Methods Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 16 cost-effectiveness studies that used empirical analysis of clinical trial data of individual patients, [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] 14 studies that used Markov modelling, [44][45][46][47][48][49][50][51][52][53][54][55][56][57] and eight that used empirical analysis based on observational data. [58][59][60][61][62][63][64][65] Two studies have used a different approach, such as extrapolating the resource use reduction that was obtained after meta-analyses of clinical trials.…”
Section: Methods Usedmentioning
confidence: 99%
“…[45,48,49,61] We discuss these studies together, because, irrespective of how the comparator is labelled, the comparator is in fact short-acting bronchodilator therapy, either used as needed or on a regular basis. All except three studies concluded that salmeterol improved health outcomes at the expense of a cost increase.…”
Section: Long-acting Inhaled B 2 -Agonist Monotherapymentioning
confidence: 99%
“…Estimates of the costeffectiveness of salmeterol versus short-acting bronchodilators or placebo ranged from cost savings of $10,152 per exacerbation avoided or $197,000 per QALY gained [9]. Six modelling studies investigated the cost-effectiveness of tiotropium versus salmeterol [12,13,[31][32][33][34]. Four studies found that tiotropium was cost saving in comparison with salmeterol in the Netherlands, Greece, Switzerland and the UK [12,31,32,34].…”
Section: Discussionmentioning
confidence: 99%
“…Six modelling studies investigated the cost-effectiveness of tiotropium versus salmeterol [12,13,[31][32][33][34]. Four studies found that tiotropium was cost saving in comparison with salmeterol in the Netherlands, Greece, Switzerland and the UK [12,31,32,34]. A study from NAIK et al [33] found the cost-effectiveness ratio to be $1,817 per exacerbation avoided in USA.…”
Section: Discussionmentioning
confidence: 99%
“…chronic and progressive dyspnoea, cough and sputum production, which result in significant impairment in exercise capacity and quality of life. 2 Worsening lungs function is also associated with frequently increasing disease severity. 3 This contributes to a more rapid decline in lungs function, 4 increased mortality and further reductions in quality of life.…”
Section: Introductionmentioning
confidence: 99%